Teacher resistance to engage with 'alternative' perspectives of difficult histories: the limits and prospects of affective disruption. Issue 5 (3rd September 2017) - Zembylas, Michalinos
ABSTRACT: This paper discusses teacher resistance to recognizing some perspectives of difficult histories. The paper focuses on the following question: How does affect contribute not only to the formation of teacher resistance, but also to its disruption in ways that enable the productive reclaiming of teachers' engagement with traumatic histories? To address this question, the paper first revisits the notion of difficult knowledge, highlighting its affective dimensions and its relevance to teacher resistance. Then, it argues that the role of affect in resistance demands a different way of conceptualizing 'teacher resistance' to acknowledge how affect is entangled with both the micro- and macro-political dimensions of resistance. In the light of this reconceptualized notion of teacher resistance, the paper theorizes the notion of 'affective disruption' by using Judith Butler's social theory. Finally, the notion of 'pedagogy of discomfort' is revisited to demonstrate the new openings created by a reconceptualized notion of teacher resistance in the context of teacher professional learning.